Aspergillus Niger Mediated Phosphocompost and Maize Production in a Greenhouse - Nyamedi, I.M (University Of Ghana, 2014)
Generally, soils in coastal savanna in Ghana are low in phosphorus (P) which affects crop growth and yield. Most phosphate rock deposits in West Africa are not reactive and therefore their direct applications do not promote readily P availability to crops. Co-composting organic waste and phosphate rock and using phosphorus solubilizing micro-organisms (PSMs) are some of the options currently attracting the attention of scientists. A study was conducted to (1) evaluate the effectiveness of Aspergillus niger, a phosphorus solubilizing microbe, in solubilizing P in phosphate rock during co-composting with organic waste (citrus waste (CW) or rice straw (RS) and (2) to evaluate the growth, dry matter production and P uptake of maize to phospho-compost application. The phospho-compost was prospered at the University of Ghana Forest and Horticulture Research Center, Okumaning near Kade. The organic waste feed stocks used were: citrus waste and rice straw. The composition of each composting pile was in the ratio of 24:3:1 w/w of feed stock, Togo phosphate rock and urea. The results showed that citrus waste feedstock was more effective than rice straw in solubilizing the P in rock phosphate. Inoculation with A. niger was not very effective in solubilizing the rock phosphate to release P to the test crop. Available P increased from week one to week four and decreased from week five to week six. During the initial days of composting, the pH of the CW compost pile with A. niger inoculation decreased from 4.6 to 2.9, while without A. niger, the pH decreased from 4.9 to 3.5. Similarly, the pH of the RS compost pile with A. niger inoculation decreased from 7.1 to 4.1, while without A. niger the pH decreased from 7.2 to 5.2. However from week5- week6 the pH increased in all the compost piles. The phospho-composts produced were evaluated using maize (Zea mays) as test crop in a pot experiment. The soil used was Toje series (Rhodic Kandiustalf). Four P rates, 0, 60, 120, and 180 kg P/ha as phospho-composts were applied per pot to a Toje series soil (Rhodic Kandiustalf). A water soluble P source Triple super phosphate (TSP) and RP with A. niger were applied at a single rate of 60 kg P/pot as control. The results suggested that A. niger + RP did not have significant effect on the vegetative parameters (plant height, girth, leaf area, dry matter yield, and plant P and Ca and Mg uptake). The CW-derived phospho-compost was more effective in promoting maize DMY compared to RS derived-compost and TSP at 60 kg P/ha, whilst the RS-derived compost was more effective at higher rate (180 kg P/ha). No significant difference in dry matter production was observed between phospho-compost inoculated with or without A. niger. At 60 kg P/ha, the trend in DMY was: CW-based phospho-compost without A. niger = CW based phospho-compost with A. niger > RS based-phospho-compost without A. niger = RS based phospho-compost with A. niger> TSP > RP with A. niger> Control. At 120 kg P/ha, the trend was: CW based phospho-compost without A. niger > RS based phospho-compost without A. niger = RS based phospho-compost with A. niger> CW based phospho-compost with A. niger. At 180 kg P/ha, the order in DMY was: RS based phospho-compost with A. niger> RS based phospho-compost without A. niger = CW based phospho-compost with A. niger> CW based phospho-compost without A. niger). P uptake followed similar trend as the DMY, and P uptake at 60 kg P/ha, was CW based phospho-compost with A. niger = CW based phospho-compost without A. niger> RS based phospho-compost without A. niger = RS based phospho-compost with A. niger = TSP > RP with A. niger> Control. No significant difference in shoot P uptake was observed between CW based phospho-compost with and without A. niger at 60 kg P/ha. The relative agronomic efficiency (RAE) for CW based phospho-compost without A. niger at 60 kg P/ha and 120 kg P/ha was 2.5 fold better than TSP. Similarly, the RAE of RS based phospho-compost with A. niger at 180 kg P/ha was 1.9 times higher than that of TSP. Further research should be conducted on the CW based phospho-compost which has proven to be more effective in promoting DMY and improved P uptake in maize
Thesis (MPhil)
Keywords: Greenhouse; Aspergillus Niger; Coastal Savanna; pH